Pengaruh Brand Image, Kepercayaan, Kepuasan Pelanggan Dan Promosi Terhadap Loyalitas Merek Smartphone Vivo (Studi Kasus Pada Masyarakat Kota Lhokseumawe) - ., Indah Safira; Ikramuddin, Ikramuddin Ikramuddin; Jullimursyida, Jullimursyida Jullimursyida (Jurnal Visioner & Strategis, 2024)
This research examines the influence of Brand Image, Trust, Customer Satisfaction and Promotion on Brand Loyalty of Vivo Smartphones in Lhokseumawe City. This research used primary data obtained by distributing questionnaires to 114 Vivo smartphone users in Lhokseumawe City. The independent variables are brand image, trust customer sarifaction, and promotion. Meanwhile, the dependent variable is brand loyalty. The data analysis technique used is multiple linear regression using SPSS (Statistical Program for Social Science) software. The research results show that Brand Image does not affect Brand Loyalty of Vivo Smartphone in Lhokseumawe City, Trust does not affect Brand Loyalty of Vivo Smartphone in Lhokseumawe City, Customer Satisfaction and Promotion positively and significantly influence Brand Loyalty of Vivo Smartphone in Lhokseumawe City. The results of testing the coefficient of determination show that brand loyalty among Vivo smartphone users in Lhokseumawe City is influenced by Brand Image, Trust, Customer Satisfaction and Promotion by 35.1 percent.